INTERNETOWA PLATFORMA DO NAUKI JĘZYKÓW DUOLINGO – OPINIE UŻYTKOWNIKÓW - Aleksandrowska, Olga; Stanulewicz, Danuta (Neofilolog, 2020)
A recent increase in the introduction and integration of information and communication technologies in education has prompted researchers to investigate the functioning and effectiveness of various digital tools. In the first part of the article, the authors present the benefits of using online platforms in language learning, with special focus on Duolingo. The second part describes the major assumptions, course design and language tasks offered by the platform. The final part concentrates on the results of a small-scale study in the form of interviews, conducted with 32 Duolingo users.